Islamic Law in Buying and Selling Second Hand Goods - Fathan Al Kubro, Muhammad; Kulsum, Umi; Khasan, Abdullah (International Proceedings of Nusantara Raya, 2024)
This study aims to examine the application of Islamic Law principles in second-hand goods buying and selling transactions. In the context of sharia economics, buying and selling is expected not only to be materially profitable, but also to fulfill fairness and transparency. This research identifies various relevant legal aspects, such as the clarity of the object of the transaction, goodwill between the seller and the buyer, and the prohibition of the practice of gharar (uncertainty) and riba (interest). Through a qualitative approach, this study analyzes the practice of selling used goods in the community, as well as the challenges faced in applying sharia principles. The results of the study show that despite the potential for violations of sharia principles, many actors try to apply the values of fairness and honesty in transactions. This research is expected to provide insight for business actors and policymakers in developing buying and selling practices in accordance with Islamic Law, as well as encourage public awareness of the importance of ethics in transactions.